2016
DOI: 10.1016/j.watres.2015.10.036
|View full text |Cite
|
Sign up to set email alerts
|

The role of aromatic precursors in the formation of haloacetamides by chloramination of dissolved organic matter

Abstract: Please cite this article as: Le Roux, J., Nihemaiti, M., Croué, J.-P., The role of aromatic precursors in the formation of haloacetamides by chloramination of dissolved organic matter, Water Research (2015), doi: 10.1016/j.watres.2015.10.036. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 40 publications
(13 reference statements)
0
16
0
1
Order By: Relevance
“…β-Alaninamide derives from the amino acid, β-alanine acid, known for generating significant yields of THMs and HANs (Hureiki et al, 1994). Hydroxybenzamide is an aromatic moiety and selected aromatic precursors have been previously shown to exhibit high N-DBP formation potentials (Le Roux et al, 2016).…”
Section: Selection Of Amidesmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Alaninamide derives from the amino acid, β-alanine acid, known for generating significant yields of THMs and HANs (Hureiki et al, 1994). Hydroxybenzamide is an aromatic moiety and selected aromatic precursors have been previously shown to exhibit high N-DBP formation potentials (Le Roux et al, 2016).…”
Section: Selection Of Amidesmentioning
confidence: 99%
“…However, recently Huang et al (2012) found that DCAcAm can be generated independently from DCAN during both chlorination and chloramination. That study suggested the need for investigating alternative pathways and potential nitrogenous and non-nitrogenous N-DBP precursors in drinking water during the application of chlor(am)ine (Chu et al, 2010a(Chu et al, , 2010bKimura et al, 2013;Le Roux et al, 2016;Nihemaiti et al, 2016). Interestingly, the DCAcAm yields reported from model precursor studies, that include amino acids, are significantly lower than those of DCAN (Chu et al, 2010b), whereas in studies that include real water matrices the levels of the two N-DBP groups are similar (mean: 1.4 µg/L and 1 µg/L, respectively) (Krasner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the simultaneous presence of chloramines and chlorine reacting with DOM can increase overall DBP production (Wang et al, 2016), and the reaction of monochloramine with DOM and other trace chemical contaminants can produce N -nitrosodimethylamine and other species such as aromatic halogenated DBPs (Pan and Zhang, 2013; Hua et al, 2015; LeRoux et al, 2016; Pan et al, 2016; LeRoux et al, 2017; Jiang et al, 2017; Tian et al, 2017) that can be more toxic than trihalomethanes and haloacetic acids, but are currently not as widely regulated (Krasner et al, 2013; Pan et al, 2013; Gong et al, 2016; Guo et al, 2016; Nihemaiti et al, 2016; Zeng et al, 2016; Spahr et al, 2017). The specific timing of chloramination in the water treatment train is thus very important; chloramines need to be generated at specific times that allows for maximum microbial inhibition while minimizing harmful DBP formation (Carlson and Hardy, 1998; Hua and Reckhow, 2007; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1978年, 美国环保局和美国国家癌症研究中心报道 称三氯甲烷对啮齿类动物具有致癌性, 此后消毒副产 物逐渐得到关注 [2] . 随着研究的深入, 越来越多的 虽然文献报道的消毒副产物已经超过600多种 [3,4] , 但在氯化消毒中仍有超过50%的总有机氯化物、臭氧 消毒中超过50%总生物可同化有机碳化合物的分子结 构尚未识别 [5,6] ; 另一方面, 即使在已经识别的DBPs中, [15,16] 、卤代乙酰胺类 [17,18] 等. Plewa等 [19] 利用GC-MS 获取分子离子和碎片离子信息, 推测出5种碘代酸(碘 [39] . Chowdhury等 [40] 利用伤残调整…”
unclassified